SENGKALAN MEMET: MAKNA PENANDA DALAM BENTUK KALIMAT ATAU GAMBAR INDAH SEBAGAI BAHASA KOMUNIKASI SENI - Febrian Wisnu Adi (Faculty of Humanities, Jember University, 2013)
Sengkalan constitutes a form of the Javanese society expressions. Sengkalan lamba has three elements, namely: sentence or words, figure, and year. Sengkalan casquette is a marker visualized in the form of pictures, patrimonies, statues, ornaments, carts representing an intention to deliver a particular message. Presenting sengkalan in a wording based on meanings and characteristics which refer to the sun, months, nature and forms to express the contents of intention loaded in the sentences. Developed from words and having presentation of word, a figur relates to synonyms, sound spelling, things and actions, similar intentions and meanings, and similarity in particular things, and so on. The substance-loads of sengkalan indicate a picture of certain situation and time, and express events occuring at particular times and places.Keywords: candrasengkala, suryasengkala, picture, ornament, figure